Implementation of Independent Learning through Literacy by Learning Video Creation Based on Smartphone for Komunitas Guru Mengajar untuk Nusantara (GUMUN) - Erwani Merry Sartika; Ratnadewi Ratnadewi; Sri Wahono; Rainisa Maini Heryanto; Markus Tanubrata; Clarence Amadeus (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
The need for an effective, efficient and creative teaching and learning process in a pandemic requires teachers and lecturers to be able to improve their ability to use technology in carrying out the learning process. This encourages community service as a form of the teaching teacher movement through empowering teachers in making learning videos. Maranatha Christian University in collaboration with Teachers for the Archipelago and STKIP PGRI initiated this activity to share with teachers throughout Indonesia. Through the strength of the community who are teachers and lecturers throughout Indonesia, the ABCD method is applied in the service of making learning videos using cellphones. The service learning method is provided by selected instructors, complementing the power of implementing community service activities. So the two service methods are the foundation of literacy in making learning videos using cellphones in the context of empowering teachers throughout Indonesia. The enthusiasm of the teachers who took part in the activity was shown by the majority expressing a desire for the activity to be held again, even though online learning was quite difficult for all participants to absorb due to various obstacles.